Biomass management targets and the conservation and economic benefits of marine reserves. Issue 2 (12th September 2012) - Yamazaki, Satoshi; Grafton, Quentin R; Kompas, Tom; Jennings, Sarah
Abstract The establishment of no‐take marine reserves has been increasingly promoted as a key measure to achieve conservation and sustainability goals in fisheries. Regardless of the wide range of benefits cited, the effectiveness of reserve establishment depends critically on fisheries management outside the reserves. We construct a bioeconomic model of a fishery that allows for the establishment of a no‐take marine reserve and evaluate how the choice of the off‐reserve management target influences the effectiveness of reserve establishment. We evaluate two biomass targets: (i) BMSY or the biomass that produces the maximum sustainable yield (MSY) and (ii) BMEY or the biomass that maximizes the net present value of the returns to fishing. The parameterized model shows that, for a wide range of scenarios, the fishery will be better off in terms of both conservation and economic objectives when the no‐take reserve is established in conjunction with the BMEY target rather than with the BMSY target. Model results further show that the opportunity cost of securing additional fish biomass, in both deterministic and stochastic environments, is lower when the reserve size is increased under the BMEY target. This finding is important because marine reserves have been established as a key measure to restore depleted fish stocks, and the results suggest that this objective can be achieved with lower economic costs in a BMEY managed fishery.